Prevalence of overweight and obesity among preschool children in Hainan: a cross-sectional study in China's largest free-trade zone - Wu, Wei-Jia; Chen, Ping-Hao; Huang, Zhen-Ning; Lei, Xue-Lu; Wang, Chen; Zhang, Chun-hui; Wang, Ping; Huang, Chui-can; Luo, Qing; Fan, Li-Chun (Frontiers in Pediatrics, 2025)
Background and aimsChildhood obesity leads to significant health risks, emphasizing the critical need for effective preventive measures during the preschool years. However, there is a lack of comprehensive studies on overweight and obesity among preschool children in Hainan Island, China's largest free-trade zone. Our study assessed the prevalence of overweight and obesity among preschool children across Hainan Island using Chinese, World Health Organization (WHO), and International Obesity Task Force (IOTF) criteria. Additionally, the potential factors influencing overweight and obesity among preschool children in Hainan Island were further explored.MethodsWe conducted a cross-sectional survey of children aged 3–6 years covering 18 cities and counties in China's largest free trade zone. The survey primarily involved anthropometric data collection and questionnaires on children's information and the sociodemographic characteristics of their parents or guardians. We recorded the height and weight of each child and calculated their body mass index (BMI). The z-score for BMI-for-age was calculated using the WHO-recommended Anthro and AnthroPlus software, and diagnoses of overweight and obesity were determined separately according to the Chinese, WHO, and IOTF criteria. The chi-squared test, t-test, or rank-sum test was applied to describe and statistically analyze the baseline characteristics of the participating children. Additionally, potential factors affecting overweight and obesity were analyzed using a multifactor binary logistic regression model.ResultsThe prevalence of overweight and obesity among preschool children in Hainan Island was 11.30% based on the Chinese criteria, significantly higher than the rates of 5.80% and 5.40% observed according to the WHO and IOTF criteria, respectively (χ2 = 12,870.368, P < 0.001). After multifactorial adjusted analyses, we found that according to the three growth criteria, having overweight fathers or mothers, family incomes of more than 100,000 Yuan, fully active eating, and higher birth weights increased the risk of overweight and obesity among preschool children in Hainan Island.ConclusionThe prevalence of overweight and obesity among preschool children in Hainan Island was lower compared to rates reported in other regions. Considering that the growth and development indicators for children under 7 years old in Hainan Island are generally lower than international standards, the use of Chinese standards may be more suitable for detecting overweight and obesity among preschool children in this area. Based on the risk factors identified in this study, preventive measures can be targeted in the future to reduce the risk of overweight and obesity in preschool children in Hainan Island.